Legal Analysis of the International Dispute Between PT Pertamina and Karaha Bodas Company - Shashia Andini Kristianto; Gunardi Lie (Universitas Ibn Khaldun Bogor, 2026)
The dispute between PT Pertamina and Karaha Bodas Company is an important example in international law practice related to investment contracts in the energy sector. This dispute originated from the collaboration on the development of a geothermal project in Karaha Bodas, which was disrupted due to Indonesian government policies during the economic crisis, leading to differing interpretations of contractual obligations and force majeure. This research aims to analyze the background of the dispute, the application of international arbitration mechanisms, and the legal implications of the arbitration award on Indonesia. The research method used is normative juridical with an approach based on legislation and case studies. The data used consists of primary, secondary, and tertiary legal materials that are analyzed qualitatively. The research results show that resolving disputes thru international arbitration provides a neutral and professional forum with final and binding decisions. However, the enforcement of arbitration awards still faces challenges, particularly in the aspect of cross-border execution. The legal implications of the arbitration ruling have a significant impact on Indonesia, particularly in increasing demands for legal certainty, investment protection, and government policy consistency. This case also underscores the importance of the principle of pacta sunt servanda in international legal relations and the state's responsibility for the actions of state-owned enterprises.